The Closure of Yale-NUS College: Unclear Reasons, Clear Implications - Loke, Hoe Yeong (International Higher Education, 2022)
Much has been made about academic freedom and financial sustainability as the reasons behind the closure of Yale-NUS College, Singapore’s much lauded liberal arts college, but these reasons are not plausible. A similarly tumultuous university closure in Singapore in 1980 may provide some pointers, if only in terms of what to expect next.